117 Beyond the divide: research on FHIR in the post-epic age. (22nd November 2019) - Bryant, William; Booth, John; Margetts, Ben; Issitt, Richard; Spiridou, Natassa
Abstract : Introduction: Prior to the rollout of the GOSH EPR system, multiple hospital databases provided fragmentary data from the clinical record. To support research in GOSH and the ICH, these data will all need to be brought together with data from the EPR to provide a complete uninterrupted clinical research dataset suitable for analysis. This need will be particularly acute for research undertaken on rare diseases where accumulating a sufficient cohort of patients is often challenging. In addition, work to harmonise with external data sources would enable more ambitious multi-site research. Method: The Digital Research Environment (DRE) Team bring together a core dataset of research–relevant clinical data comprising administrative data (e.g. patient demographics, ward stays) and clinical observations (e.g. lab results, vital signs, diagnoses) onto which we have mapped data from multiple legacy systems and the EPR. We have mapped these Research Data Views (RDVs) onto the FHIR standard for clinical data interoperability to allow harmonisation with data from other sources (such as other hospitals). Results: We have complete extractions from multiple legacy systems to produce RDVs with data back to 1st January 2000. We are now actively extracting data from the EPR aligning with these RDVs and thus are providing a continuous clinical research dataset across EPR go-live. We have >102 million events for >400, 000 patients at GOSH. These RDVs are now available via the DRE Data Selection Tool, along with complete metadata for all fields, for provision into our Research Platform for analysis. Conclusion: We have implemented a resource to put all research-relevant clinical data right at the fingertips of researchers from GOSH, ICH and beyond. This will feed into research projects big and small, empowering researchers to focus on the science, rather than the manual collection of data.